Auditoría del sistema de gestión de calidad del proceso de mantenimiento de unidades de ala fija de una compañía aeronáutica - Pazmiño Sión, Julio Alfonso (2010)
This article is based on an audit process to the maintenance management system of a private flying organization. First describes the background to the work and its importance, in addition to why we choose the holding area for fulfillment. We analyze what the current status of the institution, the general processes of the club. Determining a quality policy and then implement all procedures that are missing from the organization, determine roles and responsibilities within the maintenance process, setting all the documentation of the maintenance management and developing a maintenance management manual. After this is determined by an audit process with all these procedures is determined by the expected results by improving the management all maintenance. As a result of the paper provides conclusions and recommendations of all the improvements made within the maintenance management.